MicroRNA, an Antisense RNA, in Sensing Myeloid Malignancies - Setijono, Stephanie Rebecca; Kwon, Hyog Young; Song, Su Jung (Frontiers in Oncology, 2018)
Myeloid malignancies, including myelodysplastic syndromes (MDS) and acute myeloid leukemia (AML), are clonal diseases arising in hematopoietic stem or progenitor cells. In recent years, microRNA (miRNA) expression profiling studies have revealed close associations of miRNAs with cytogenetic and molecular subtypes of myeloid malignancies, as well as outcome and prognosis of patients. However, the roles of miRNA deregulation in the pathogenesis of myeloid malignancies and how they cooperate with protein-coding gene variants in pathological mechanisms leading to the diseases have not yet been fully understood. In this review, we focus on recent insights into the role of miRNAs in the development and progression of myeloid malignant diseases, and discuss the prospect that miRNAs may serve as a potential therapeutic target for leukemia.